The detailed transseptal puncture technique for optimal closure in patients with a patent foramen ovale - Ilkay, Erdogan; Sariçam, Ersin; Kaçmaz, Fehmi; Yakici, Aysel; Koca, Çiğdem; Özeke, Özcan; Polat, Melike; Güney, Murat Can; Karaduman, Bilge Duran; Erdöl, Mehmet Akif; Onal, Mehmet Zulkuf (Frontiers in Cardiovascular Medicine, 2024)
BackgroundThe closure of a patent foramen ovale (PFO) using transseptal puncture has particular advantages and disadvantages. Thus, transseptal puncture should be re-evaluated in detail.AimsWe aimed to assess the effectiveness of the detailed transseptal puncture technique in patients who underwent PFO closure due to cryptogenic stroke or transient ischemic attack in terms of residual shunts and atrial fibrillation.MethodsWe prospectively analyzed 144 consecutive patients who underwent PFO closure by the detailed transseptal puncture technique between February 2013 and April 2023 in two centers. All of the patients had a >10 mm long-tunnel PFO.ResultsThe procedural success rate was 100%. However, after the procedure, moderate pericardial effusion developed in one patient (0.7%) and an acute pulmonary embolism related to femoral vein thrombosis was observed in one patient (0.7%) during the first month. Complications related to the procedure were noted in two patients (1.4%) during the first month of follow-up. Residual shunts were observed in 1.4% of cases after PFO closure.ConclusionWe demonstrated that the detailed transseptal technique is safe and effective for PFO closure. The detailed transseptal PFO closure technique significantly reduced the risk of atrial fibrillation, and the occurrence of residual shunts was significantly low following the closure.